Biomedical Applications of Magnetic Levitation. Issue 3 (8th December 2021) - Dabbagh, Sajjad Rahmani; Alseed, M. Munzer; Saadat, Milad; Sitti, Metin; Tasoglu, Savas
Abstract : Magnetic levitation (MagLev) is a user‐friendly, electricity‐free, accurate, affordable, and label‐free platform for chemical and biological applications owing to its ability to suspend and separate a wide range of diamagnetic materials (e.g., plastics, polymers, cells, and proteins) based on their density. Various MagLev designs (e.g., standard, single and double ring, titled, and rotational MagLev setups) are presented in the literature with a trade‐off between sensitivity and detection range. Herein, various MagLev designs, the advantages and pitfalls of each method, and current challenges encountered by MagLev platforms are reviewed. Moreover, end applications of MagLev are presented in single‐cell and protein analysis, diseases diagnosis (e.g., cancer and hepatitis C), tissue engineering, 3D self‐assembly, and forensic case studies to provide an insight regarding the potentials of MagLev. Abstract : The magnetic levitation technologies covering various designs, advantages and pitfalls of each method, and current challenges encountered by MagLev platforms are reviewed. End applications are presented in single‐cell and protein analysis, diseases diagnosis (e.g., cancer and hepatitis C), tissue engineering, 3D self‐assembly, and forensic case studies to provide an insight regarding the potentials of MagLev.